An experimental investigation of the triaxial shear behaviors of silt-based foamed concrete. (December 2021) - Zhang, Hongbo; Liu, Mingpeng; Shuo, Zhang; Zhao, Zhizhong; Sun, Yuhai; Song, Xiuguang; Wang, Hao; Zhang, Xinyi; Wu, Jianqing
Abstract: The silt-based foamed concrete, in which the cement is partially replaced with silt, has become a novel material in road construction projects. However, at the present time, only a few studies have been completed in which attention was paid the shear strength of the aforementioned type of material in subgrade applications. Therefore, in order to address those issues, this research investigation conducted triaxial shear tests. During the experimental testing processes, the mechanical behaviors of silt-based foamed concrete specimens were examined. Such influencing factors as wet density, silt content and confining pressure levels were considered in the experiments. As indicated by the stress-strain curves of the silt-based foamed concrete, the material had performed well in the elastoplastic model results. The stress-strain curves of the silt-based foamed concrete had displayed both hardening and softening phenomena. In addition, the peak strength and residual strength were observed to both increase to average levels of 0.82 MPa and 0.62 MPa, respectively, as the density increased to 100 kg/m 3 . Meanwhile, the peak and residual strength levels decreased the mean levels of 16.8% and 12.3%, respectively, when the silt content was increased by 10%. It has been found that the addition of silt will transform pore structures from uniformly distributed sphericity into irregular combined broken bubbles. In addition, increases in silt content could potentially increase the size of pores. The values of the cohesion and friction angles have been observed to greatly increase with higher density levels. The increases in silt content will decrease cohesion. However, the impacts of silt content on friction angles have been found to be complex. In the present research, the shear strength levels corresponding to different normal stress levels were determined.